Antimicrobial efficacy of wedelia glauca (ortega) o. Hoffm. Ex hicken and phytochemical analysis using gas chromatography – mass spectrometry - KRISHNAVIGNESH L,; MAHALAKSHMIPRIYA A, (International Journal of Pharma and Bio Sciences, 2017)
Plants as a treasure of bioactive compounds continue to play a major role in sustaining human health. The aim of this study is to evaluate the antimicrobial efficacy of Wedelia glauca stem extracts against the pathogens causing urinary tract infections and to screen them to identify the phytochemical constituents present in the extracts. Individual extraction was done by soxhlation using five solvents. Agar well diffusion method was used to determine the antimicrobial activity. Preliminary phytochemical analysis revealed the presence of alkaloids, flavonoids, carbohydrates, proteins & amino acids, steroids, triterpenoids, tannins, reducing sugar, and saponins in different plant stem extracts. Most of the extracts were shown substantial inhibition activity against Gram-positive compared to gram-negative bacteria. Acetone extract showed better activity against all the bacterial and fungal cultures studied. The GC- MS analysis of acetone extract revealed the presence of various potential compounds which attributes to the results obtained.